2015
DOI: 10.1016/j.jneumeth.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Methodology and effects of repeated intranasal delivery of DNSP-11 in a rat model of Parkinson's disease

Abstract: Background To circumvent the challenges associated with delivering large compounds directly to the brain for the treatment of Parkinson’s disease (PD), non-invasive procedures utilizing smaller molecules with protective and/or restorative actions on dopaminergic neurons are needed. New Method We developed a methodology for evaluating the effects of a synthetic neuroactive peptide, DNSP-11, on the nigrostriatal system using repeated intranasal delivery in both normal and a unilateral 6-hydroxydopamine (6-OHDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
4
20
0
Order By: Relevance
“…; Stenslik et al . ). DNPSs and mature GDNF promote similar actions in neurons, in contrast to pBDNF and mBDNF which display opposing effects.…”
Section: A Prodomain As An Independent Signaling Ligand: Pbdnfmentioning
confidence: 97%
See 1 more Smart Citation
“…; Stenslik et al . ). DNPSs and mature GDNF promote similar actions in neurons, in contrast to pBDNF and mBDNF which display opposing effects.…”
Section: A Prodomain As An Independent Signaling Ligand: Pbdnfmentioning
confidence: 97%
“…The significance of these findings is relative as the endogenous NGF prodomain has not been found yet in neural tissues or primary neurons. Apart from the neurotrophin family, another growth factor prodomain has been tested for activity: fragments of the glial cell line-derived neurotrophic factor (GDNF) prodomain, carrying the term dopamine neuron stimulating peptides (DNSP), has also been shown to be active as they display robust neurotrophic actions similar to mature GDNF (Bradley et al 2010;Stenslik et al 2015). DNPSs and mature GDNF promote similar actions in neurons, in contrast to pBDNF and mBDNF which display opposing effects.…”
Section: A Prodomain As An Independent Signaling Ligand: Pbdnfmentioning
confidence: 99%
“…Therefore, this peptide can be promising for the treatment of late-stage PD patients. In this study, DNSP-11 was delivered directly into the brain, and it is unknown if it can penetrate through the blood-brain barrier and reach target neurons if injected systemically [94], but it was speculated that the systemic delivery of DNSP-11 will be unsuccessful due to a short half-life of the peptide in rat plasma (<12 min) [95]. However, it was shown that DNSP-11 retains its neuroprotective activity in the dopamine system in a 6-OHDA model of PD when delivered intranasally [95].…”
Section: Peptides From the Gdnf Proregion With An Unknown Mechanism Omentioning
confidence: 99%
“…DNSP-11 seems to be a promising alternative for further preclinical development, as it is relatively small. The receptor and signaling mechanism for DNSP-11 is yet to be determined [94], as well as the delivery strategy, as it is unlikely to produce sufficient brain exposure upon systemic delivery due to its short half-life [95]. Possibly, it can be delivered intranasally [95].…”
Section: Advantages and Limitations In The Use Of Each Class Of Gfrα/mentioning
confidence: 99%
“…Therefore, new avenues need to be examined that overcome challenges associated with delivering large MW compounds to the brain for the treatment of chronic, progressive neurodegenerative diseases and disorders [1, 2, 9]. One possible alternative strategy currently under investigation is the discovery and development of new neuroactive compounds [35–38] that can potentially be delivered to the CNS using non-invasive routes of administration, such as intranasal delivery [1, 39].…”
Section: 0 Introductionmentioning
confidence: 99%